2008
DOI: 10.1007/s10530-008-9277-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a shift in life-history strategy during the secondary phase of a plant invasion

Abstract: We investigated the correlated response of several key traits of Lythrum salicaria L. to water availability gradients in introduced (Iowa, USA) and native (Switzerland, Europe) populations. This was done to investigate whether plants exhibit a shift in life-history strategy during expansion into more stressful habitats during the secondary phase of invasion, as has recently been hypothesized by Dietz and Edwards (Ecology 87(6): 1359, 2006). Plants in invaded habitats exhibited a correlated increase in longevit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The shifts in habitat preference or tolerance associated with invasions have been recognized in previous studies (e.g. Hejda et al, 2009;Moloney et al, 2009), and various explanations have been suggested (Molina-Montenegro et al, 2011). In some cases, rapid evolution in the invaded range may occur, leading to changes in habitat preference or tolerance (Reznick & Ghalambdor, 2001;Lee, 2002;Lambrinos, 2004;Lavergne et al, 2009;Novy et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…The shifts in habitat preference or tolerance associated with invasions have been recognized in previous studies (e.g. Hejda et al, 2009;Moloney et al, 2009), and various explanations have been suggested (Molina-Montenegro et al, 2011). In some cases, rapid evolution in the invaded range may occur, leading to changes in habitat preference or tolerance (Reznick & Ghalambdor, 2001;Lee, 2002;Lambrinos, 2004;Lavergne et al, 2009;Novy et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Chun et al 2009;Moloney et al 2009). Within each range, seeds were used from three geographically distant regions and within each region we used three populations (Table 1).…”
Section: Plant Materials and Experimental Crossesmentioning
confidence: 99%
“…In this context, the increased leaf life span of A. negundo under more stressful conditions (Reich et al 1992;Westoby et al 2002) can be considered an adaptation typical of the For statistical details see Table 5 Mean values (±SD) refer to mean data by origin type (n = 5 populations) secondary phase of invasion, following the theory of Dietz and Edwards (2006). One of the few supports of this conceptual model until now was recently provided by Moloney et al (2009) in an observational approach. The authors studied life-history traits of purple loosestrife (Lythrum salicaria) along a water availability gradient both in the introduced and in the native range and found smaller growth habit of Lythrum salicaria combined with increased longevity in dry habitats compared to wet ones.…”
Section: Traits Of Primary and Secondary Invasionmentioning
confidence: 99%